2021
DOI: 10.1038/s41396-021-00906-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial diversity–biomass relationships are driven by soil carbon content across global biomes

Abstract: The relationship between biodiversity and biomass has been a long standing debate in ecology. Soil biodiversity and biomass are essential drivers of ecosystem functions. However, unlike plant communities, little is known about how the diversity and biomass of soil microbial communities are interlinked across globally distributed biomes, and how variations in this relationship influence ecosystem function. To fill this knowledge gap, we conducted a field survey across global biomes, with contrasting vegetation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
107
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(162 citation statements)
references
References 80 publications
10
107
0
4
Order By: Relevance
“…The relationship between biomass and community diversity is not unidirectional. Under scarce resources with low biomass, the relationship between the two can be positive, whereas the presence of dominant species under high biomass will reduce the diversity [43] . Both iron and sodium have been linked previously with plant–microbe-soil interactions.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between biomass and community diversity is not unidirectional. Under scarce resources with low biomass, the relationship between the two can be positive, whereas the presence of dominant species under high biomass will reduce the diversity [43] . Both iron and sodium have been linked previously with plant–microbe-soil interactions.…”
Section: Discussionmentioning
confidence: 99%
“……), animal wastes, urban and cleans [1][2][3]. Biomass resources are of high water and oxygen content, low density, low calorific value; These features negatively affect the quality of loss [4]. The negative properties of biomass can be eliminated by physical processes (size reduction-crushing and grinding, drying, filtration, aggregation) and transformation processes (biochemical and thermochemical processes) [5].…”
Section: Introductionmentioning
confidence: 99%
“…The negative properties of biomass can be eliminated by physical processes (size reduction-crushing and grinding, drying, filtration, aggregation) and transformation processes (biochemical and thermochemical processes) [5]. Biomass energy stands out with its various advantages such as the ability to be grown almost everywhere, good knowledge of production and conversion technologies, suitability for energy production every time, adequacy of low light intensities, being storable, adequacy of temperatures between 5 and 35°C, being in socioeconomic developments, not creating environmental pollution (Very low NO x and SO 2 emissions), less greenhouse effect formation compared to other energy sources, cream of CO 2 balance in the atmosphere, not causing acid rain [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, mixing chemically contrasting crops may provide a greater number of niches for microorganisms to exploit, which allows functionally dissimilar microbial communities to coexist, and thus result in a greater microbial diversity and biomass than might be expected from the average of the individual communities that are supported by monocultures (Chapman and Newman, 2010). Although greater diversity not always linked to greater biomass, a recent meta-analysis found that in temperate regions, where soil is not rich in C, greater microbial diversity is usually associated with greater microbial biomass due to facilitation and niche partitioning by supporting the co-existence of multiple microbial species (Bastida et al, 2021). An increased microbial diversity could increase the probability of including taxa particularly influential in extracellular enzyme production for nutrient mining and SOM degradation through metabolic and co-metabolic processes.…”
Section: Introductionmentioning
confidence: 99%
“…An increased microbial diversity could increase the probability of including taxa particularly influential in extracellular enzyme production for nutrient mining and SOM degradation through metabolic and co-metabolic processes. Furthermore, an increased microbial biomass could also result in stronger SOM mineralization as a consequence of increased microbial metabolic activity (Bastida et al, 2021). Thus, mixtures of crop residues could enhance the extent to which soil microbial communities mine nutrients for SOM and lead to a greater priming effect.…”
Section: Introductionmentioning
confidence: 99%